Rožmarinska kislina - Sova, Matej (Farmacevtski vestnik, 2012)
Rosmarinic acid, an ester of caffeic acid and 3,4-dihydroxyphenyllactic acid, is an active component of several medicinal plants and spices. This article presents the biosynthesis of rosmarinic acid and provides a brief description of its main biological activities and potential therapeutic use.
Keywords: biosinteza; lastnosti; rožmarinska kislina